ENHANCING FINANCIAL BEHAVIOR OF GENERATION Z: THE ROLE OF FINANCIAL LITERACY AND MANAGEMENT IN MEDAN CITY - Adi Harianto; Deva Djohan; Atika Rahmi; Yogi Rahman Feriza Ginting; Fachrun Nissa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the impact of financial literacy and financial management on the financial behavior of Generation Z in Medan City. Financial literacy is expected to enhance individuals' understanding of better financial management, which in turn can influence their financial behavior. This study uses a quantitative approach with a survey method. Data collection was done through questionnaires distributed to 200 respondents who are Generation Z in Medan City. Data analysis techniques used include multiple linear regression to test the relationships between variables. The results indicate that both financial literacy and financial management have a positive and significant impact on the financial behavior of Generation Z. These findings suggest that improving financial literacy and sound financial management can enhance responsible financial behavior among Generation Z. This study provides important implications, both in the development of theories related to financial literacy and financial behavior, and in the practical management of personal finances for young generations.